El proceso evaluativo en programas con modalidad innovadora - Martínez de Acosta Carmen H. (Universidad Nacional de Colombia, 1999)
This study has an exploratory, descriptive, categoric design by which a content analysis was done in order to identified and categorizes different quantitative and qualitative indicators for the evaluation of Master' s Program in an innovative modality. The following categories where proposed: organizational, curricular, and professional profile. The study was, done with an integrate framework in which it is an expectation that the evaluation helps in the decision making process. The sample selection was done by convenience and it included 10 national and 5 international academic programs at Specialization and Magister level, all of them in innovative modalities. The results reflected 5 categories and 34 indicators for the evaluation of the organizational component; 13 categories and 57 indicators for the evaluation of the curricular component; and 5 categories and 26 indicators for the evaluation of the occupational component. As a final result, all of the indicators where Iinked together in an integrated evaluation proposal in which the categories and indicators are shown as well as the need of implementation by theconstruction of an evaluation process with a critical, participate and plural approach. El estudio corresponde a un diseño de tipo exploratorio, descriptivo, categórico. Mediante el análisis de contenido se identificaron y categorizaron diferentes indicadores cuantitativos y cualitativos para la evaluación de los componentes organizacional, curricular y de desempeño del programa de maestría, en modalidad innovadora dentro del marco de una conceptualización integral en la cual se espera que el proceso evaluativo apoye la toma de decisiones. De manera intencional, la muestra seleccionó diez programas académicos nacionales y cinco internacionales que ofertan programas a nivel de especialización y maestría en modalidades innovadoras. Los resultados arrojaron cinco categorías y treinta y cuatro indicadores para el componente  organizacional, trece categorías y cincuenta y siete indicadores para el curricular, y cinco y veintiséis respectivamente para el componente de desempeño. Éstos constituyen una propuesta de evaluación integral que presenta exclusivamente categorías e indicadores, evidenciando la necesidad de complementarlo mediante la construcción de un proceso evaluativo, crítico, participativo y plural.